Pelaksanaan Kawin Bajapuik Dan Uang Hilang Di Kabupaten Padang Pariaman - Rahmat Putra Syahyu Razak; Dahlil Marjon; Yasniwati Yasniwati (LPPM Universitas Ekasakti Padang, 2023)
Marriage is an event in the life of every human being. Marriage that occurs between a man and a woman will have both physical and spiritual consequences between them, on society and also disputes with assets acquired between them both before, during and after the marriage takes place. Marriage according to customary law is a very important matter because it does not only involve the relationship between the two parties of the bride and groom, but also concerns the family relationship between the two parties. In the area of ​​West Sumatra, specialy in Padang Pariaman Regency, there is a uniqueness in the marriage system, namely the